What about customer service innovation in the digital era?. (14th December 2022) - Youssef, Afef Ben
Increasingly, customer service is considered by many managers as the best way to gain insight into customers and take advantage of service propositions for superior performance. In fact, customer service is a core component of the customer experience. Besides, it seems that technologies are helping them to keep this orientation, since frequent changes in customer expectations are more and more putting pressure and new challenges on the customer service offer. Thus, the aim of this paper is to identify antecedents and outcomes of customer service innovation. Using survey research, a total of 141 responses was received from Tunisian firms and was used in the data analysis. Findings show that customer orientation and commitment to customer service influence the firm adoption of customer service innovation. In addition, the positive impact of customer service innovation on the firm's market performance was confirmed and the ICT capability moderates this relationship.